DETERMINANTS OF STATE TAX HAVEN UTILIZATION: EMPIRICAL STUDY ON BANKING COMPANIES - Catherine, Lisa (Widya Mandala Surabaya Catholic University, 2024)
Research Purposes. This study aims to test the determinants of the utilization of tax haven countries. The determinants are multinational companies, intangible assets, and good corporate governance (GCG). We use bank healthy rate as control variable. Research Methods. The research is quantitative research, with the population is banks listed on the Indonesia Stock Exchange 2016-2020. The sample used as many as 125 banking companies with purposive sampling technique. Hypothesis testing using logistic regression analysis. Research Results and Findings. The results show that intangible assets have a positive effect on the use of tax haven countries. Multinational, GCG, and performance have no effect on the utilization of tax haven countries. This study concludes that banks use their intangible assets to reap the tax facilities in tax haven countries.